Interview with Milton Santos - Scarim, Paulo Cesar (Geografares, 2025)
Interview conducted with Professor and geographer Milton Santos on March 14, 2000, by Paulo Cesar Scarim, as part of a master’s thesis defended at the University of São Paulo (USP) in 2000, under the supervision of Professor Ana Fani Alessandri Carlos.
Keywords: Epistemology; History of Thought; Critical Geography; Decoloniality